2017
DOI: 10.1097/mao.0000000000001510
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod (FTY-720) is Capable of Reversing Tumor Necrosis Factor Induced Decreases in Cochlear Blood Flow

Abstract: FTY-720 is capable of reversing changes in cochlear blood flow induced by application of TNF. This makes FTY-720 a valid candidate for potential treatment of numerous inner ear pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…Consequently, it has been shown that cochlear microcirculation may actually recover from TNF-induced decreases by application of JTE-013, FTY-720, or etanercept. 22,45 In conclusion, we were able to prove that LPS decreases cochlear microcirculation in a dose-dependent manner. Moreover, this effect is at least in parts mediated by the TNF pathway.…”
Section: Independent Of How High the Concentration Of Lps Was Appliedmentioning
confidence: 57%
See 2 more Smart Citations
“…Consequently, it has been shown that cochlear microcirculation may actually recover from TNF-induced decreases by application of JTE-013, FTY-720, or etanercept. 22,45 In conclusion, we were able to prove that LPS decreases cochlear microcirculation in a dose-dependent manner. Moreover, this effect is at least in parts mediated by the TNF pathway.…”
Section: Independent Of How High the Concentration Of Lps Was Appliedmentioning
confidence: 57%
“…Hence, etanercept is a viable candidate for clinical treatment of otitis media with suppurative labyrinthitis, even if a recent shift in hearing threshold has already been diagnosed. Consequently, it has been shown that cochlear microcirculation may actually recover from TNF‐induced decreases by application of JTE‐013, FTY‐720, or etanercept 22,45 …”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…This animal model has repeatedly been used to address numerous question in relation with cochlear microcirculation (20)(21)(22). Anesthesia was induced by a single injection of ketamin/xylazine (85 mg/kg and 8.5 mg/kg bodyweight, respectively) and kept up by repeated injection of half the above dose every 30 minutes.…”
Section: Anesthesia and Surgical Preparationmentioning
confidence: 99%
“…elektrischen Signalen durch die Haarzellen nicht mehr möglich ist (Thalmann et al 1972;Konishi 1979). Auch die An-- und Abwesenheit von Zytokinen wie beispiels-weise dem Tumornekrosefaktor--α nimmt über Vermittlung von weiteren Signal-kaskaden Einfluss auf den cochleären Blutfluss (Scherer et al 2010;Bertlich et al 2017).…”
Section: Das Hörvermögen In Abhängigkeit Vom Cochleären Blutflussunclassified